As contribuições do ensino de matemática para a manutenção do sistema capitalista - Kuhn, Leticia Diello (2023)
This work aims to understand the contributions of Mathematics teaching in Brazil to support the necessary conditions for the maintenance of the Capitalist System. The research had a qualitative approach and focused on a case study. Semi-structured interviews were carried out with teachers in the area of Mathematics who work in public and private schools and in the Final Years of Elementary and High School and their speeches were interpreted according to the theoretical assumptions of Discourse Analysis of the French matrix. The analysis made it possible to identify four functions assigned to the school that establish favorable conditions for the maintenance of the capitalist system: the propagation of values pertinent to the ruling classes, individual guidance to students, preparation for the job market and stimulation of critical thinking. In addition, the identification of teachers as working class was also subject to analysis, since this category is not immune to the control mechanisms pertinent to the maintenance of capitalism. It was concluded that mathematics education contributes as an instrument of submission and training to follow rigid and unquestionable orders and that success in relation to this discipline - which is not necessarily linked to performance in the discipline, but to the student's degree of adjustment to the school system - seems to guarantee better jobs in the labor market, which makes it play a fundamental role in maintaining inequalities. Thus, the teaching of mathematics can be considered as a powerful tool of control and power over the new generations of the working class.